2022
DOI: 10.1002/smtd.202200581
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Conductive Metal−Organic Frameworks Nanotubes for Ultrahigh‐Performance Flexible NO Sensors

Abstract: Additionally, the number of Cu 2c (the Cu 2c in the crystal defects bound with two S atoms) in the Cu-BHT structure is the primary factor affecting the Cu-BHT-based sensing devices' performance. [6,17] However, the Cu-BHT's crystal structure makes its specific surface smaller than that of the conventional metal-organic frameworks, which significantly affects its application in electrocatalysts and sensors. Thus, the preparation of Cu-BHT with a large surface area and abundant Cu 2c on the surface is a crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…The binding energies (BE) of 953.1 and 932.3 eV correspond to the Cu 2p 1/2 and 2p 3/2 regions, respectively. As shown in Figure f, the Cu 2p 3/2 region shows a main peak at 932.6 eV with a shoulder at higher BE and no significant satellite peaks, thus pointing to the exclusive presence of Cu I , in line with previously reported X-ray photoelectron spectroscopy (XPS) measurements of Cu-BHT. ,,,, Since the sputtered starting material is predominantly composed of CuO with a minor fraction of Cu 0 (Figure S12), the reduction of Cu II to Cu I must occur during the vapor–solid reaction with H 6 BHT. Based on previous studies of Cu-thiolate self-assembled mono- and multilayers, , we hypothesize that first CuO can be reduced via the oxidation of the thiol groups in H 6 BHT to disulfides, followed by the formation of Cu–thiolate bonds with the excess vaporized linkers.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The binding energies (BE) of 953.1 and 932.3 eV correspond to the Cu 2p 1/2 and 2p 3/2 regions, respectively. As shown in Figure f, the Cu 2p 3/2 region shows a main peak at 932.6 eV with a shoulder at higher BE and no significant satellite peaks, thus pointing to the exclusive presence of Cu I , in line with previously reported X-ray photoelectron spectroscopy (XPS) measurements of Cu-BHT. ,,,, Since the sputtered starting material is predominantly composed of CuO with a minor fraction of Cu 0 (Figure S12), the reduction of Cu II to Cu I must occur during the vapor–solid reaction with H 6 BHT. Based on previous studies of Cu-thiolate self-assembled mono- and multilayers, , we hypothesize that first CuO can be reduced via the oxidation of the thiol groups in H 6 BHT to disulfides, followed by the formation of Cu–thiolate bonds with the excess vaporized linkers.…”
Section: Resultssupporting
confidence: 85%
“…As shown in Figure 2f, the Cu 2p 3/2 region shows a main peak at 932.6 eV with a shoulder at higher BE and no significant satellite peaks, thus pointing to the exclusive presence of Cu I , in line with previously reported X-ray photoelectron spectroscopy (XPS) measurements of Cu-BHT. 15,37,44,45,47 Since the sputtered starting material is predominantly composed of CuO with a minor fraction of Cu 0 (Figure S12), the reduction of Cu II to Cu I must occur during the vapor−solid reaction with H 6 BHT.…”
Section: Resultsmentioning
confidence: 99%
“…The response rate of NO 2 gas detection was significantly improved (from 122% to 1053% at 30 ppm), along with ultra-low LOD (∼2.3 ppb) and good gas selectivity. Wang 18 prepared DPPTT/Cu-BHT nanotubes heterostructure OFET-based sensors. The sensors had excellent selectivity for NO toxic gas, up to 13 610%, the LOD of 5 ppb.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wang et al developed a sensing device based on Cu-BHT nanotubes, which showed excellent selectivity and sensitivity in the detection of NO. 35 Hence, we take the metal−organic framework Cu-BHT monolayer nanostructure as a representative model to conduct a first-principles investigation to comprehensively understand the reduction reaction mechanism of NO to NH 3 catalyzed by TM-BHT. In contrast to copper metal, the Cu-BHT monolayer nanostructure boasts a significantly larger specific surface area, resulting in a substantially higher density of active sites.…”
Section: Introductionmentioning
confidence: 99%